(untitled) (Nigerian Journal of Technology, 2020)
Investigation of microwave drying of sweet potato slices was conducted at microwave oven power settings of 90, 100, 120 Watts and slice thicknesses of 3mm, 4mm and 6mm using Fourier models and response surface methods. The slice samples dried from initial moisture content of 70.71 to 12.7 final (equilibrium) moisture content in the microwave oven. Fourier models adequately fitted the drying data with the following values of the fit parameters: MBE= 0.00002943 to 0.000645, R² = 0.9987 to 1, RMSE = 0.00384 to 0.01692. Effective moisture diffusion coefficient ( of the samples ranged from m2/s to m2/s. Analysis of Variance (ANOVA) was used to analyze the effect of drying conditions on the samples parameters at 95% ( p<0.05). The results showed that slice thickness and microwave power have significant effects on the ash and fiber contents of the dried potato samples. At the microwave power of 90 W and slice thickness of 4 mm the values of Fiber and Ash retained in the dried sweet potato samples were optimal at 4.30% and 2.50% respectively, after drying for 390 minutes to an average moisture content of 14.2 gH2O/gdm. Optimized equations for predicting the percent ash and fiber contents at combined factors of microwave power and slice thickness were developed using Response Surface Methodology (RSM) at 95% confidence bound. The coefficients of determination (R2) for the models are 0.7333 and 0.9655 for fiber and ash respectively. These are indications that the models can be used to predict the two food components of microwave dried potato slices. http://dx.doi.org/10.4314/njt.v39i3.36